Decoupling the spread of grasslands from the evolution of grazer-type herbivores in South America - Strömberg, Caroline A. E. (2013)
The evolution of high-crowned cheek teeth (hypsodonty) in herbivorous mammals during the late Cenozoic is classically regarded as an adaptive response to the near-global spread of grass-dominated habitats. Precocious hypsodonty in middle Eocene (∼38 million years (Myr) ago) faunas from Patagonia, South America, is therefore thought to signal Earth's first grasslands, 20 million years earlier than elsewhere. Here, using a high-resolution, 43-18 million-year record of plant silica (phytoliths) from Patagonia, we show that although open-habitat grasses existed in southern South America since the middle Eocene (∼40 Myr ago), they were minor floral components in overall forested habitats between 40 and 18 Myr ago. Thus, distinctly different, continent-specific environmental conditions (arid grasslands versus ash-laden forests) triggered convergent cheek-tooth evolution in Cenozoic herbivores. Hypsodonty evolution is an important example where the present is an insufficient key to the past, and contextual information from fossils is vital for understanding processes of adaptation.